Amino-functionalized Fe/Co bimetallic MOFs for accelerated Fe (III)/Fe (II) cycling and efficient degradation of sulfamethoxazole in Fenton-like system - Zhang, Xianbing; Liu, Yuheng; Yuan, Jiajia (Frontiers in Chemistry, 2025)
Metal-organic frameworks (MOFs) are recognized as important Fenton-like materials for environmental remediation. However, their applications are often hindered by slow cycling between Fe (III) and Fe (II). This study aimed to address the slow Fe (III)/Fe (II) cycling limitation of Fe-MOFs through dual modification strategy: bimetallic modification and amino functionalization. A series of NH2-MOF(Fe, Co) catalysts with varying Fe/Co ratios were synthesized via a hydrothermal method and evaluated for sulfamethoxazole (SMX) degradation. The optimized NH2-MOF(Fe, Co) catalyst (Fe/Co ratio = 7:3) exhibited substantially enhanced catalytic performance, with SMX removal rate and rate constant in the H2O2 system being 3.2 and 43.5 times higher than those of the Fe-MOF/H2O2 system, respectively. The catalyst demonstrated robust performance across a wide pH range (3.05–7.00), addressing a common limitation of Fenton-like systems. Physicochemical characterization revealed that the enhanced performance was attributed to two key factors: the synergistic effect between Co and Fe in the bimetallic active center, and improved electron transfer to the central metal due to -NH2 functionalization. These modifications effectively addressed the Fe (III)/Fe (II) redox cycling limitation. The proposed reaction mechanism provides insights into SMX degradation pathways in the NH2-MOF(Fe, Co)/H2O2 system. This study presents an efficient and stable MOF-based Fenton-like catalyst with potential applications in wastewater treatment and environmental remediation.